2017
DOI: 10.3892/ol.2017.7322
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR up‑regulates chemokine (C‑C motif) ligand 2 and promotes proliferation of macrophages and myeloid‑derived suppressor cells in hepatocellular carcinoma cell lines

Abstract: Abstract. Accumulating evidence demonstrated that Hox antisense intergenic RNA (HOTAIR) serves essential roles in the development and metastasis of several types of cancer. In hepatocellular carcinoma (HCC), high expression of HOTAIR is associated with poor prognosis, and HOTAIR regulates cell migration and proliferation. However, the downstream molecular targets of HOTAIR depend on the cancer cell types, and little is known about the precise molecular mechanisms of HOTAIR involved in cancer development. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…In recent years, many studies have shown that lncRNAs play important roles in gene regulation, transport, differentiation, dosage compensation, and protein synthesis. [8][9][10] The lncRNA SNHG1 is upregulated in many cancers. 7 For example, lncRNA HOX transcript antisense RNA has been verified as an effective diagnostic marker in patients with liver, colon, breast, and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have shown that lncRNAs play important roles in gene regulation, transport, differentiation, dosage compensation, and protein synthesis. [8][9][10] The lncRNA SNHG1 is upregulated in many cancers. 7 For example, lncRNA HOX transcript antisense RNA has been verified as an effective diagnostic marker in patients with liver, colon, breast, and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that noncoding RNAs (including lncRNAs and miRNAs) are crucial for tumorigenesis and tumor progression. 21 , 22 Previous studies have shown that lncRNA GAS5 expression was downregulated in gastric cancer; furthermore, upregulation of GAS5 expression is known to suppress cell proliferation. 23 In this study, we found that expression of GAS5 was downregulated in PC tissue compared with adjacent normal pancreatic tissues ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Hox antisense intergenic RNA overexpression in hepatocellular carcinoma cell lines Li-7 and Hep3B led to an increase in CCL2 expression in these cells. Subsequent coculture of these cells with peripheral blood mononuclear cells (PBMCs) led to PBMC differentiation to CD14+HLA-DR-CD33+CD11b+ MDSCs (162). However, abolishing this effect, for example, using anti-CCL2 blocking antibodies, was not tested.…”
Section: Ccl2 Impacts Myeloid Cell Maturation and Differentiationmentioning
confidence: 99%